2015
DOI: 10.1371/journal.ppat.1005270
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Blockade Differentially Impacts Regulatory T Cells from HIV-Infected Individuals Depending on Plasma Viremia

Abstract: Blocking the PD-1/PD-L1 pathway has emerged as a potential therapy to restore impaired immune responses in human immunodeficiency virus (HIV)-infected individuals. Most reports have studied the impact of the PD-L1 blockade on effector cells and neglected possible effects on regulatory T cells (Treg cells), which play an essential role in balancing immunopathology and antiviral effector responses. The aim of this study was to define the consequences of ex vivo PD-L1 blockade on Treg cells from HIV-infected indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Differences in response to inhibitory receptor blockade treatment have also been shown in murine studies and in human T cells from HIV-infected subjects, where not all individuals responded equally to treatment2425. Therefore, the potential usefulness of HIV-specific CD8 + T cells to eliminate target cells in immune based curative strategies requires further investigation with a particular emphasis of the T cell exhaustion process, including the role of TIGIT.…”
mentioning
confidence: 97%
“…Differences in response to inhibitory receptor blockade treatment have also been shown in murine studies and in human T cells from HIV-infected subjects, where not all individuals responded equally to treatment2425. Therefore, the potential usefulness of HIV-specific CD8 + T cells to eliminate target cells in immune based curative strategies requires further investigation with a particular emphasis of the T cell exhaustion process, including the role of TIGIT.…”
mentioning
confidence: 97%
“…Interestingly, PD‐L1 blockade during chronic LCMV or HIV infection results in exaggerated expansion of Treg cells and up‐regulation of inhibitory markers . These data demonstrate that the PD‐1 pathway not only inhibits exhausted CD8 T cells, but also inhibits Treg cells.…”
Section: Treg Cells and Pd‐1 Can Also Play Beneficial Roles By Limitimentioning
confidence: 79%
“…While initial studies of latency reversing agents showed limited induction of viral RNA expression in vivo [81], new reagents like GS-9620, a TLR-7 agonist developed by Gilead, seem very promising and may prove useful with CAR T cell therapies [82]. Furthermore, since HIV-specific CD4+ and CD8+T cells can lose their effector functions and proliferative capacity in a phenomenon known as immune exhaustion [83] mediated by programed death 1 (PD-1), blockade of the PD-1 pathway may restore impaired anti-HIV immune responses [84], [85]. This may be of particular importance for cell-based therapies such as anti-HIV CAR T cells.…”
Section: Discussionmentioning
confidence: 99%